Calculati:
a) 7·{7+7·[7⁶₋(7²)³+11]}+2·7²₋3·23=
b) (9+3⁴:9²):10+81·82:41:3³₋(2013²⁰¹⁴)⁰=
c)18176:71₋3·(29·24₋23·30)+11⁷:11⁵=
d) (84084:42+13):403+9·[85085:11₋3·(73·16₋1143)].

Va rog ajutati-ma! Si daca vreti ca sa va fie mai usor puteti sa dati raspunsul direct..

2

Răspunsuri

2014-11-11T22:10:38+02:00
A)7·{7+7·[7⁶₋(7²)³+11]}+2·7²₋3·23=7·{7+7·[7⁶₋ 7^{6}  +11]}+2·7²₋3·23=
  7·[7+7·(0+11)]+2·7²-3·23= 7·(7+7·11)+2·7²-3·23=7·84+2·49-69=588+98-69=617
b) (9+81:81):10+81·82:41:27-1=10:10+81·82:41-1=1+6642:41:27-1=
1+162:27-1=1+6-1=6
c)256-3·(696-690)+ 11^{2} =256-3·6+121=256-18+121=359
d)(2002+13):403+9·[7735-3·(1168-1143)=2015:403+9·(7735-3·25)=5+9·7660=
5+68940=68945


2 2 2
2014-11-11T23:17:07+02:00